PTVR – A software in Python to make virtual reality experiments easier to build and more reproducible - Castet, Eric; Termoz-Masson, Jérémy; Vizcay, Sebastian; Delachambre, Johanna; Myrodia, Vasiliki; Aguilar, Carlos; Matonti, Frédéric; Kornprobst, Pierre (Journal of vision (Charlottesville, Va.), 2024)
Researchers increasingly use virtual reality (VR) to perform behavioral experiments, especially in vision science. These experiments are usually programmed directly in so-called game engines that are extremely powerful. However, this process is tricky and time-consuming as it requires solid knowledge of game engines. Consequently, the anticipated prohibitive effort discourages many researchers who want to engage in VR. This paper introduces the Perception Toolbox for Virtual Reality (PTVR) library, allowing visual perception studies in VR to be created using high-level Python script programming. A crucial consequence of using a script is that an experiment can be described by a single, easy-to-read piece of code, thus improving VR studies' transparency, reproducibility, and reusability. We built our library upon a seminal open-source library released in 2018 that we have considerably developed since then. This paper aims to provide a comprehensive overview of the PTVR software for the first time. We introduce the main objects and features of PTVR and some general concepts related to the three-dimensional (3D) world. This new library should dramatically reduce the difficulty of programming experiments in VR and elicit a whole new set of visual perception studies with high ecological validity.